Absorptive capacity and cooperation evidence in innovation from public policies for innovation - Moura, Dulcineia Catarina (2020)
Purpose – The purpose of this paper is to better understand whether firm cooperation and absorptive capacity foster success in seeking public financial support for innovation activities and, by doing so, how they contribute to innovation output. Design/methodology/approach – The authors therefore extend the existing literature focusing on the effects of cooperation and absorptive capacity on specific public financial support for innovation activities in Portuguese firms from local or regional government, central administration and the European Union by using available data from the Community Innovation Survey CIS 2010 and the application of logistic regression models. The empirical analysis enabled a better understanding of the positive relationship of the variables that determine the form of public financial support in the integration of incentives within firms to stimulate innovation. Findings – Therefore, as the level of absorptive capacity in Portuguese firms increases, so does the demand for benefits from public financial support to stimulate innovation from the European Union also increases. The same analysis, now considering the determinant cooperation, notes the positive effects of institutional sources of information and cooperation, in the propensity for seeking public financial incentives from the Central Administration and the European Union. As for internal information and cooperation sources, they are positively related to the integration of incentive measures from the local or Regional Administration and Central Administration. Originality/value – The paper presents results that allow us to propose some suggestions that both the firms and those responsible for the implementation of public policies can undertake to increment innovation performance.